2005
DOI: 10.1523/jneurosci.4530-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Apoptotic, Glucocorticoid Receptor Cochaperone Protein BAG-1 Is a Long-Term Target for the Actions of Mood Stabilizers

Abstract: Increasing data suggest that impairments of cellular plasticity/resilience underlie the pathophysiology of bipolar disorder. A series of microarray studies with validating criteria have recently revealed a common, novel target for the long-term actions of the structurally highly dissimilar mood stabilizers lithium and valproate: BAG-1 [BCL-2 (B-cell CLL/lymphoma 2)-associated athanogene]. Because BAG-1 attenuates glucocorticoid receptor (GR) nuclear translocation, activates ERK (extracellular signal-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 36 publications
3
62
0
Order By: Relevance
“…Hippocampal homogenates collected from rats immediately after death (i.e., absolute control animals) showed a distinctive band with a MW of ∼32 kDa. This isoform corresponds well with one of the three bands identified in rodent tissue (Zhou et al, 2005). An identical band of ∼32 kDa was also detected in the hippocampus of postmortem rats maintained at either 24 °C or 4 °C storage temperatures.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Hippocampal homogenates collected from rats immediately after death (i.e., absolute control animals) showed a distinctive band with a MW of ∼32 kDa. This isoform corresponds well with one of the three bands identified in rodent tissue (Zhou et al, 2005). An identical band of ∼32 kDa was also detected in the hippocampus of postmortem rats maintained at either 24 °C or 4 °C storage temperatures.…”
Section: Resultssupporting
confidence: 67%
“…Whether increases in Bag 1 activity can also be traced to changes in temperature in vivo is not known. The observation that administration of lithium and valproate increases the expression of Bag 1 by inhibiting the glucocorticoid receptor in the rat hippocampus (Zhou et al, 2005), raises the possibility that hypothermia might be an additional factor in modulating the activity of Bag 1. Schematic diagram of the experimental steps instituted for studying postmortem variables and Bag 1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…169,170 In addition to lithium's effects on a number of intracellular cascades, lithium also induces the expression of BDNF and subsequent activation of TrkB, the receptor for BDNF, in cortical neurons. The activation of BDNF/TrkB signaling is essential for the neuroprotective effects of this drug.…”
Section: Neurotrophic Effects Of Lithium and Divalproexmentioning
confidence: 99%
“…Interest in BAG-1 as a putative mediator of affective resilience initially arose out of microarray studies which demonstrated that two agents that are structurally highly dissimilar -lithium and valproate -increased levels of BAG-1 mRNA, protein and function (Zhou et al, 2005). BAG-1 exerts three functions that make it potentially noteworthy in the pathophysiology and treatment of BD:…”
Section: Construct Validitymentioning
confidence: 99%